2020
DOI: 10.21873/invivo.11977
|View full text |Cite
|
Sign up to set email alerts
|

Picrasma quassioides Extract Elevates the Cervical Cancer Cell Apoptosis Through ROS-Mitochondrial Axis Activated p38 MAPK Signaling Pathway

Abstract: Background/Aim: Picrasma quassioides (P. quassioides) is used in traditional Asian medicine widely for the treatment of anemopyretic cold, eczema, nausea, loss of appetite, diabetes mellitus, hypertension etc. In this study we aimed to understand the effect of P. quassioides ethanol extract on SiHa cervical cancer cell apoptosis. Materials and Methods: The P. quassioides extract-induced apoptosis was analyzed using the MTT assay, fluorescence microscopy, flow cytometry and western blotting. Results: P. quassio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Additionally, the MAPK signaling pathway, which governs cell proliferation, differentiation, apoptosis, and inflammation, has been implicated in the pathogenesis of various diseases when dysregulated (25). Activation of ERK, JNK, and p38 MAPK by ROS is known to affect cellular responses, including apoptosis (26,27). We observed marked phosphorylation of these MAPKs in response to CDDP, indicating their involvement in the apoptotic process induced by the drug in Vero cells.…”
Section: Discussionmentioning
confidence: 61%
“…Additionally, the MAPK signaling pathway, which governs cell proliferation, differentiation, apoptosis, and inflammation, has been implicated in the pathogenesis of various diseases when dysregulated (25). Activation of ERK, JNK, and p38 MAPK by ROS is known to affect cellular responses, including apoptosis (26,27). We observed marked phosphorylation of these MAPKs in response to CDDP, indicating their involvement in the apoptotic process induced by the drug in Vero cells.…”
Section: Discussionmentioning
confidence: 61%
“…The p38 phosphorylation inhibitor and NAC (ROS scavenger) significantly reduced the occurrence of apoptosis compared to ERK and JNK inhibitors (Figure 4). It has been reported that P. quassioides promotes apoptosis in SiHa cervical cancer cells by activating the p38/MAPK signaling pathway, which provides an effective theoretical basis for the β-CCE (monomer of P. quassioides) inducing SiHa cell apoptosis (40). However, this study has some limitations.…”
Section: Discussionmentioning
confidence: 87%
“…However, it is worth noting that the ethanolic extracts of Picrasma quassinoides, a species of Picrasma native to Asia, showed cytotoxic effect for SiHa (cervical cancer) (Gong et al, 2020) and HepG2 G12V cells (liver cancer) (Xie et al, 2020), indicating an effect dependent on the species, soil and/or climate in which these species grow. From the adjusted curve of the data obtained for the crude extract of Pau Tenente (Figure 1), it was possible to obtain the polynomial of Equation 2.…”
Section: Crude Extractmentioning
confidence: 99%